Pengaruh Non Farm Payroll, Suku Bunga Bank Sentral Amerika Serikat (The Fed), dan Indeks Nikkei 225 Terhadap Indeks dari Saham-saham Perusahaan Berbasis Syariah di Jakarta Islamic Index - Edhy Priyatna Anugrah Surbakti; Lauw Tjun Tjun (Jurnal Akuntansi)
As a result of globalization, the current capital markets respond to information both domestically and globally as a consideration to make investment decisions. There are several indicators of international economic fundamentals are commonly used as consideration in making investment decisions. The purpose of this research is to determine whether the level of non-farm payroll, the interest rate the U.S. central bank (the Fed), and the NIKKEI 225 index is partially and simultaneously have a significant impact on the index of shares sharia-based company (incorporated in Jakarta Islamic Index). The data used is the data non-farm payroll rate, the interest rate the U.S. central bank, and the NIKKEI 225 index. Data were analyzed using multiple linear regression method. Research results, the authors conclude that non-farm payroll rate, the interest rate the U.S. central bank, and the NIKKEI 225 index is partially and simultaneously significantly affect the Jakarta Islamic Index.